The Quality of Today's Textbooks: Central-Regional Collaboration for 21st-Century Education - Budi Rahayu Setiawan; Usep Kuswari; Yatun Romdonah Awaliah; Haris Santosa Nugraha (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Textbooks serve as a mandatory guide in the teaching and learning process in schools, one example is the Panggelar Basa Sunda textbook for Senior High School class XII. The purpose of this study is to analyze the quality of textbook content. The method used uses a descriptive qualitative approach. The source of data in this study is the Panggelar Basa Sunda textbook for Grade XII High School. Data was obtained through documentation techniques. The results of this study explain that the Panggelar Basa Sunda textbook for Senior High School Class XII has met the content quality indicators in accordance with the 2022 Education Standards, Curriculum, and Assessment Agency [Badan Standar, Kurikulum, dan Asesmen Pendidikan]. These indicators include scientific accuracy, conformity with local content set by the governor, alignment with the development of science and technology, relevance to the context and environment, and coherence among the content sections of the book. In addition, it is also collaborated with the Jabar Masagi program as an implementation of the local content of the Merdeka Curriculum. Therefore, the textbooks are in line with the quality of content required by 21st century education. The implications of this research provide benefits for students and teachers in using textbooks in schools and a form of synergy between the central and local governments.